Psychological Support in the Midst of VUCA Situations for Generation Z in the Finnish Education System - Eva Latipah (Jurnal Pendidikan Agama Islam)
Purpose – This study aims to identify the forms of psychological support provided by the Finnish education system to Generation Z in facing VUCA situations and analyze the strategies applied within the Finnish education system to strengthen the psychological resilience and adaptability of Generation Z in the VUCA era.